A Review On Perspectives Of Electrochemical Sensors In Next-Generation Healthcare - T, Yasodha; T, Menaka; M.S, Vijayalakshmi; A, Sangeetha (Journal of Neonatal Surgery, 2025)
Impacts of sensors have increasing demand in various fields such asagriculture,environment,healthcare,medicine and pharmacology. Electrochemical approaches as a sole platform or integrated with metal organic frameworks/nanomaterials provide promising technologies due to their simplicity, high sensitivity and specificity. Electrochemical sensors have paved the way for emerging novel technologies in early stage diagnosis of diseases through its related biomarkers and biochemicals.Hence our primary focus is to review novel technologies for the early-stage detection and diagnosis of diseases (cancer,cardiovascular and diabetes ) related biomarkers such as alpha-fetoprotein, hemin, glucose, uric acid,hydrogen peroxide and nicotine. Our review aims to provide insights of integrated electrochemical sensors with metal organic frameworks (MOF), nanomaterials and microfluidics. The new era of digital health depends on various bioanalytical techniques through swift processes that produce reliable results.Hence this paper outlines and summarize the advancements in electrochemical approach that are applicable in healthcare and medicine...